A propósito de los experimentos mentales: una tentativa para la construcción de explicaciones en ciencias - Aguilar M, Yirsen; Romero, Ángel E. (Revista Científica, 2011)
In the analysis in some research is done to show how the experiment has been established since the Middle Ages, a powerful strategy for the construction of scientific explanations. In the seventeenth century thought experiments are highlighted, such as Galileo, Descartes, Newton and Leibniz (Brown, 1986; Koyré 1968, Kuhn 1964, 246-252). In modern times, the creation of quantum mechanics (Kühne, 2005, pp 280-317, Popper, 1959) and relativity (Brown, 1987; Norton, 1991 and 1993) are almost unthinkable without the crucial role of thought experiments. In 1811, in an essay Hans Christian Ørsted is the first to use the term Gedankenexperiment (experiments conducted in thought) to refer to a special source of knowledge (cf. Ørsted, 1811), and was also the first Gedankenversuch use the German equivalent in 1820. Years later, Ernst Mach used the term differently Gedankenexperiment to denote only imagined driving a real physical experiment and hence the contrast between physical experiments and the experiment. In this respect we can say that was Ernst Mach who coined this term in the philosophical discussion (Mach, 1897). This term is used by Mach (1948) in a broad sense. According to him, outside the physical testing (empirical), the man who reaches an advanced intellectual development, often uses mental experimentation. However, this type of experiment is unusual in the teaching of physics. With didactic intentions, an analysis of the historical and epistemological perspective Mach (1948) on the grounds that their particular way of taking these experiments, allows reframing these in the teaching of physics. In this perspective, the experiment is assumed as the construction of a hypothetical scenario where they represent circumstances or events that arise from consequences created by the subject also from conjecture to respond to an intentionality. In terms, the experiment can be assumed as an act of thought which values the experience preserved for the memory and language, ie, the thought experiment becomes a resource of imagination for creating and viewing possible worlds. From the analysis of classic situations like the fall of bodies in Galileo, the bucket of water to illustrate Newton's absolute space, sets some features, functions and legitimacy of the experiments. Educational implications are finally established that thought experiments can illustrate and experiment show that an attempt may be suitable for physics education.